Ti/Al‐based contacts to p‐type SiC and GaN for power device applications. Issue 4 (11th November 2016) - Roccaforte, F.; Vivona, M.; Greco, G.; Lo Nigro, R.; Giannazzo, F.; Di Franco, S.; Bongiorno, C.; Iucolano, F.; Frazzetto, A.; Rascunà, S.; Patti, A.; Saggio, M.
Abstract : Metal contacts (Schottky or Ohmic) to p‐type wide band gap (WBG) semiconductors SiC and GaN are important for power devices technologies. This work reports on the properties of Ti/Al‐based contacts to p‐type 4H‐SiC and p‐type GaN, monitored using different techniques and test‐patterns. In particular, in the case of p‐type SiC, Ti/Al and Ti/Al/W contacts showed a superior Ohmic behavior after annealing at 900–1100 °C (with ρ c  ≈ 1.5–6 × 10 −4  Ωcm 2 ), attributed to the formation of Ti‐ and Al‐containing phases at the interface and in the stack. Due to the lower ρ c with respect to Ni‐based contacts, Ti/Al allowed a reduction of the forward voltage drop in 4H‐SiC p–n junctions. On the other hand, in the case of p‐type GaN, Ti/Al contacts exhibited a higher barrier height (2.08 eV) with respect to Ni contacts. Hence, they can be promising as Schottky gates in high electron mobility transistors (HEMTs). However, temperature‐dependent electrical measurements revealed a decrease of the barrier height down to 1.60 eV upon annealing at 800 °C, with an increase of the leakage current in test‐diodes. This result provided an important indication for the practical use of Ti/Al gate electrodes for the fabrication of normally off HEMTs with a p‐GaN gate.